Access, Uptake, and Use of CSA and CIS Tools Disseminated through AICCRA Regional Capacity Building Initiatives in Eastern and Southern African Countries - Ambaw, Gebermedihin; Tesfaye, Abonesh; Recha, John W.M.; Magagula, Futhi; Radeny, Maren A.O.; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in collaboration with regional, national partners such as the Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA), the Center for Coordination of Agricultural Research and Development for Southern Africa (CCARDESA), IGAD Climate Prediction & Applications Centre (ICPAC), African Climate Policy Center (ACPC), World Meteorological Organization (WMO) Regional Office for Africa, International Research Institute for Climate and Society (IRI), The Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF), national Ministries of Agriculture, Universities, National Meteorological and Hydrological Services (NMHSs), and SADC Climate Services Centre (SADC-CSC) has been disseminating and building capacity on various decision support tools (DSTs). The tools include the Crop Capability and Yield Prediction Tool, Sub-seasonal forecasting using PyCPT, Soil Health Monitoring, and Digital Soil Mapping (DSM) using R Studio, and were disseminated as part of regional capacity building to participants from 14 countries, namely Botswana, Burundi, Cameroon, Eswatini, Ethiopia, Lesotho, Madagascar, Malawi, Mozambique, Namibia, Somaliland, Uganda, Zambia, and Zimbabwe, representing 34 institutions since 2022. This study assessed the access, uptake, and use of the DSTs tools in Eastern and Southern African countries through a survey. The results show that the tools have excellent access, uptake, and use across the countries. In addition, the impact of these tools has been clear in many areas. The Crop Capability and Yield Prediction Tool, for example, has improved extension advisories, supported agricultural planning, and contributed to research and curriculum development. Similarly, the Sub-seasonal Forecasting using PyCPT tool has contributed to early warning systems, seasonal planning, and climate risk management, with direct applications in disaster preparedness and farmer advisories. The Soil Health Monitoring and DSM using RStudio tool has improved soil management practices, fertilizer management, and soil degradation monitoring, highlighting its importance for sustainable soil management.